The Effect of the Problem-Based Learning Model on Critical Thinking Skills and Student Learning Outcomes - Hendra Alsa Fahmi; Amiruddin Siahaan; Ira Suryani (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to analyze the effect of implementing Problem-Based Learning (PBL) on students’ critical thinking skills and learning outcomes in the Fiqh Ibadah course at the Faculty of Islamic Studies, Universitas Dharmawangsa. A quasi-experimental approach with a pretest–posttest control group design was employed. The research participants consisted of 45 fourth-semester students divided into an experimental group taught using the PBL model and a control group taught using conventional instructional methods. Research instruments included a critical thinking skills test, a cognitive learning outcomes test, and an observation sheet of learning activities. Data were analyzed using normality and homogeneity tests, independent-samples t-tests, and two-way ANOVA with the assistance of SPSS version 26.0. The findings indicate that the implementation of Problem-Based Learning has a statistically significant effect on improving students’ critical thinking skills (p < 0.05) and learning outcomes in the Fiqh Ibadah course (p < 0.05). Furthermore, a significant interaction was found between the learning model and students’ critical thinking skills in influencing learning outcomes. These results demonstrate that PBL not only enhances students’ conceptual understanding but also fosters higher-order thinking abilities, including analytical, reflective, and contextual reasoning in addressing contemporary fiqh issues. Therefore, Problem-Based Learning is recommended as an effective instructional strategy for improving the quality of Islamic education learning in higher education